The melting sea - Hunter, Erin (Hunter, Erin. Seekers, return to the wild ;, 2012)
"Toklo, Kallik, Lusa, and Yakone trek onward toward the Melting Sea, the site of Kallik's traumatic cubhood--and prepare to be separated for the first time since their journey began"--